Teses e Dissertações sobre Habitação na Pos-Graduação da FAUUSP - Sampaio, Maria Ruth Amaral de (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2000)
The graduate course of the School of Architecture and Urbanism of the University of São Paulo has produced a series of dissertations and theses on housing problems. These studies adopt different approaches which are, in part, a result of the three areas of knowledge in the program of the faculty: History, Project and Technology. This diversity in approach and focus is also a result of the political, economic and cultural development of the country and its implications in different periods, as well as of the introduction of foreign ideas. In ad dition to these factors, the acceleration of urban growth, especially in São Paulo and in other large Brazilian cities, has made the problems of housing much more visible and alarming, thus stimulating diverseb points of view in the academic production encountered